Metagenomic survey reveals global distribution and evolution of microbial sialic acid catabolism - Li, Yisong; Fan, Yeshun; Ma, Xiaofang; Wang, Ying; Liu, Jie (Frontiers in Microbiology, 2023)
Sialic acids comprise a varied group of nine-carbon amino sugars found mostly in humans and other higher metazoans, playing major roles in cell interactions with external environments as well as other cells. Microbial sialic acid catabolism (SAC) has long been considered a virulence determinant, and appears to be mainly the purview of pathogenic and commensal bacterial species associated with eukaryotic hosts. Here, we used 2,521 (pre-)assembled metagenomes to evaluate the distribution of SAC in microbial communities from diverse ecosystems and human body parts. Our results demonstrated that microorganisms possessing SAC globally existed in non-host associated environments, although much less frequently than in mammal hosts. We also showed that the ecological significance and taxonomic diversity of microbial SAC have so far been largely underestimated. Phylogenetic analysis revealed a strong signal of horizontal gene transfer among distinct taxa and habitats, and also suggested a specific ecological pressure and a relatively independent evolution history in environmental communities. Our study expanded the known diversity of microbial SAC, and has provided the backbone for further studies on its ecological roles and potential pathogenesis.